Fermentasi Produksi Asam Sitrat menggunakan Aspergillus Niger ATCC 16404 dengan Substrat Hidrolisat Cair Limbah Padat Industri Brem - Kusuma, Gede Asstaradi; Antara, Nyoman Semadi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p13, 2019)
Dregs of solid waste brem industry contained 12 percent of sugar and 10,8 percent of starch. Component contained in the dregs are expected to produce citric acid. The aims of this study were to determine the effect of static cultivation on the production of citric acid from liquid hydrolyzate brem waste by using Aspergillus niger. The experimental design used in this study was a simple randomized block design (RAK), which the static cultivations (0, 1, 2, 3 days) as a treatment. The results showed that the static cultivation treatment significantly affected the level of acidity (pH), total soluble solids, biomass, reducing sugar, calcium citrate, citric acid and yield. The static cultivation for 1 day was the best treatment to produce Ca-citrate which the production level was 3,84 ± 0,05 g/L. By the stoichiometry method the citric acid production could be calculated, which equal to 2,12 ± 0,03 g/L. Keywords: Aspergillus niger, dregs of brem, static cultivation, Ca-citrate, citric acid